Correlation between the HBsAg level and the peripheral blood lymphocytes profile in chronic Hepatitis B patients from Malaysia - Hadi, Qabas Naemah; Mustafa Mahmoud, Mohammed Imad Al-Deen; Jaafar, Khairul Azhar; Hui, Yee Chee (SciTechnol, 2016)
Background